Knowledge, Attitudes, and Uptake of Cervical Cancer Screening Among Female Students and Staff at a Tertiary Institution in Northern Uganda: A Cross‐Sectional Study - Milton Anguyo; Morrish Obol Okello; David Komakec; Emmanuel Alyoomu; Habert Aziku; Ruth Catherine Ouma; Pebalo Francis Pebolo (Health Science Reports, 2026)
ABSTRACT Background and Aims Cervical cancer remains a leading cause of cancer‐related deaths among women in low‐resource settings like Uganda. Screening is essential for early detection and prevention, yet knowledge, attitudes, and uptake among university females are poorly understood. This study aimed to investigate knowledge, attitudes, and uptake of cervical cancer screening among females at a tertiary institution in Northern Uganda. Methods A cross‐sectional quantitative study was conducted at a tertiary institution in Northern Uganda, involving 335 females aged 25–49 years (students and staff) selected via stratified random sampling (from a calculated target of 336; one questionnaire was excluded for incompleteness). Data were collected using a structured questionnaire and analyzed with Stata version 17 (StataCorp, College Station, TX, USA). Descriptive statistics summarized knowledge, attitudes, and uptake. Logistic regression examined factors associated with screening uptake. All statistical tests were two‐sided, and a p < 0.05 was considered statistically significant. Results A total of 335 women (median age 27 years, IQR 26–30) were analyzed. Awareness of cervical cancer was almost universal (97.9%, 328/335), with health institutions the commonest information source (50.0%, 164/328). Overall, 83.3% (279/335) demonstrated good knowledge, although knowledge of specific items such as HPV and screening methods was substantially lower. Attitudes were mixed: 52.5% (176/335) negative and 47.5% (159/335) positive towards screening. Uptake of cervical cancer screening was 31.3% (105/335). Among the unscreened (68.7%, 230/335), barriers included lack of screening‐location information (84/230, 35.4%), pain concerns (78/230, 32.9%), perceived good health (56/230, 23.6%), and shyness (19/230, 8.0%). In multivariable logistic regression, older age (aOR 1.11, 95% CI 1.05–1.18, p < 0.001) and being staff (aOR 2.37, 95% CI 1.15–4.92, p = 0.02) were significantly associated with higher screening uptake. Conclusion Despite high overall knowledge, more than half of participants demonstrated negative attitudes toward screening, and uptake remained low, revealing a substantial knowledge–attitude‐practice gap. Targeted education to University females and improved service access interventions are recommended to enhance screening and reduce cervical cancer burden.